Chondrite diversity revealed by chromium, calcium and magnesium isotopes. (1st February 2023) - Zhu, Ke 朱柯; Schiller, Martin; Moynier, Frédéric; Groen, Mirek; Alexander, Conel M.O'D.; Davidson, Jemma; Schrader, Devin L.; Bischoff, Addi; Bizzarro, Martin
Abstract: Chondrites are undifferentiated meteorites that can provide information on the compositions of materials in the early solar System, including the building blocks of the terrestrial planets. While most chondrites belong to well-defined groups based on their mineralogy and chemical composition, a minor fraction have unusual characteristics and are classified as ungrouped chondrites. These ungrouped chondrites reflect the diversity of chondritic materials in the early solar system; however, they are not as well studied as grouped meteorites and their origins are poorly understood. In this study, we present high-precision mass-independent Cr, Ca and Mg isotope data for 17 ungrouped chondrites. The ε 54 Cr and ε 48 Ca (ε expresses parts per ten thousand mass-independent isotope deviation) data for ungrouped chondrites also provide important constraints for assessing their relationships to the known chondrite groups, and the radiogenic Mg isotope ratios (μ 26 Mg*) can be used to track the early solar system history. We also present the first high-precision data for a Kakangari (KC) chondrite, an enstatite chondrite, and for four enstatite-rich meteorites. The ε 54 Cr and ε 48 Ca values for the KC are −0.44 ± 0.04 and −1.30 ± 0.25, respectively, and ε 48 Ca value for SAH 97096 (EH3) is −0.19 ± 0.22 that overlaps with that of those of Earth-Moon system and ordinary chondrites. All the carbonaceous chondrite-like (CC) ungrouped chondrites show positive ε 54 Cr and ε 48 Ca values, and all the non-carbonaceous chondrite-like (NC) ungrouped chondrites and KCs (also belong to the NC trend) show zero or negative ε 54 Cr and ε 48 Ca values. This observation confirms the CC-NC dichotomy for primitive solar system materials. LEW 87232 (KC) also shows the highest 55 Mn/ 52 Cr ratio and ε 53 Cr value amongst all the chondrites. There is a positive trend between 55 Mn/ 52 Cr ratios and ε 53 Cr values among all the chondrites that mostly reflects a mixing between multiple chondritic components. Previously it has been reported that there is a bulk 26 Al- 26 Mg correlation line amongst chondrites. This correlation has been interpreted as being due to mixing of CAIs (high 27 Al/ 24 Mg ratios and μ 26 Mg* values) and other silicate material (e.g., chondrules and matrix). By providing additional 26 Al- 26 Mg chondrite data, we show that there is no 26 Al- 26 Mg correlation line for the chondrites, ruling out the two-endmember (i.e., CAIs and other silicates) mixing model.